2015
DOI: 10.1111/dote.12428
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms in PTEN and additional gene-gene interaction with risk of esophageal squamous cell carcinoma in Chinese Han population

Abstract: This study aims to investigate the association of five single nucleotide polymorphisms (SNPs) in the phosphatase and tensin homologue (PTEN) gene and additional role of gene-gene interaction with esophageal squamous cell carcinoma (ESCC), based on a Chinese case-control study. A total of 871 subjects (420 males and 451 females) were selected, including 425 ESCC cases and 446 controls. Five SNPs were selected for genotyping in the case-control study: rs2735343, rs555895, rs2299939, rs17431184 and rs701848. Logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…The major finding was a significant association of PTEN rs701848 TC/CC genotypes and C allele and AKT rs2494752 AG/AA genotype with an increased BC risk under a dominant model in a relatively large cohort (n=920). Our finding that PTEN rs701848 polymorphism predicted the individual susceptibility to the development of BC is similar to the results from the studies reported in other tumors such as colorectal cancer, esophageal squamous cell carcinoma (ESCC)[8, 12, 22]. PTEN rs701848 SNP is located at 3′-UTR region, which can be targeted by microRNAs, and might alter the strength of microRNAs binding site near the SNP rs701848, thus influencing gene regulation and protein expression.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The major finding was a significant association of PTEN rs701848 TC/CC genotypes and C allele and AKT rs2494752 AG/AA genotype with an increased BC risk under a dominant model in a relatively large cohort (n=920). Our finding that PTEN rs701848 polymorphism predicted the individual susceptibility to the development of BC is similar to the results from the studies reported in other tumors such as colorectal cancer, esophageal squamous cell carcinoma (ESCC)[8, 12, 22]. PTEN rs701848 SNP is located at 3′-UTR region, which can be targeted by microRNAs, and might alter the strength of microRNAs binding site near the SNP rs701848, thus influencing gene regulation and protein expression.…”
Section: Discussionsupporting
confidence: 88%
“…Lin’ study on colorectal cancer (CRC) [12] reported that patients with rs701848 TC/CC genotype in the dominant model and C allele were more likely to be increased CRC risk than carrying CC genotype patients. Xu et al [8] revealed that the carriers of homozygous mutant of rs701848 polymorphism increased ESCC risk than those with wild-type homozygotes. It is worthy to note that in another 2 case-control studies, one observed that the distribution of genotypes or alleles at PTEN rs701848 T/C possessing notably higher proportion in ESCC cases (n=304) than in the controls (n=413) [6], however, the other study did not found any significant differences of the genotype in PTEN rs701848 in ESCC patients (n=226) [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Recently, progress has been made in diagnosis and therapeutic options for ESCC, particularly in exploring its relationship with gene polymorphisms. 17 , 18 PIM1 is a proto-oncogene that encodes a serine/threonine kinase with multiple cellular functions involving the regulation of cell apoptosis and progression, as well as transcription through various signaling pathways, including the STAT3 → PIM1 → NFkappaB stress response pathway and signaling pathways downstream of Akt. 19 21 Accumulating evidence has demonstrated that PIM1 plays an important role in tumor progression, including colon cancer, laryngeal cancer, lymphocytic leukemia, and head and neck squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Two common methods for the detection of real-time qPCR products are: (1) non-specific fluorescent dyes that intercalate with any double-stranded DNA, such as SYBR Green method, This method is a low cost and accurate way for detection of gene copy number alteration (CNA), including copy number amplification 31 and deletion 32 ; (2) sequence-specific DNA probes consisting of oligonucleotides that are labelled with a fluorescent reporter which permits detection only after hybridization of the probe with its complementary sequence, such as TaqMan probe method. A series of TaqMan Assays were designed to detect SNP 33 , CNA 34 and gene mutation. This method contains a specific DNA probe, which improves the specificity and sensitivity for detection, with a wider application, a higher accuracy than SYBR Green method, however, a higher cost.…”
Section: The Most Common Used Chromosomal and Genomic Technologies Inmentioning
confidence: 99%